Evaluation of Building Construction Approval Policy in Pademangan District - Ichsan Ziddan Alfarizi; Ika Widiastuti (Universitas Muhammadiyah Ponorogo, 2026)
This study evaluates the implementation of the Building Construction Approval Policy (PBG) in Pademangan District, North Jakarta. The transition from a Building Construction Permit (IMB) system to a PBG system aims to simplify bureaucracy and support orderly and legal urban development. However, this change faces several challenges, particularly in densely populated areas like Pademangan, which has many unlicensed buildings. Using William Dunn's policy evaluation theory and descriptive-qualitative methods, this study assesses the effectiveness, efficiency, equity, responsiveness, adequacy, and appropriateness of the PBG policy. Data collection techniques included interviews with officials and residents, field observations, and literature studies. The results indicate that although the digital SIMBG system improves transparency and efficiency, public understanding of the PBG procedure remains low. Technical barriers, limited digital access, and a lack of government outreach are key obstacles. On the other hand, government initiatives in implementing online systems and providing public services have been supporting factors. This study concludes that the PBG policy in Pademangan needs to be optimized, particularly in terms of outreach and institutional coordination to ensure equitable access, legal compliance, and sustainable urban development. Keywords: PBG Policy; IMB; Building Permits;